A general method for preparing intact nuclear DNA. - Cook, P (1984)
Naked nuclear DNA is easily sheared. Two general methods are described for preparing intact DNA in a stable form that can be pipetted without breaking it. Cells are encapsulated in agarose microbeads and then lysed in a non-ionic detergent (i.e., Triton X-100) and 2 M NaCl or an ionic detergent (e.g., sodium or lithium dodecyl sulphate) in low salt. Most cellular protein and RNA then diffuse out through pores in the beads to leave encapsulated and naked DNA which is nevertheless accessible to enzymes and other probes. Remarkably, considerable structure is preserved since the DNA is supercoiled and chromosomes retain their shape.